Transformational Leadership With Moon Character: Empirical Evidence At STIEM Bongaya Campus - Abdi Akbar (Jurnal Manajemen, 2022)
The leadership style at STIEM Bongaya is transformational leadership with a moon character not found on other campuses in Makassar City. We examine the role of involvement and the proactive role of transformational leadership relationships with employee performance. The reason for choosing the object is because the characteristics of ownership are family owned and are directed by second-generation family members, so it is interesting to study. This study used a sample of 83 employees to obtain accurate information in analyzing data by using WarpPLS 5.0.Â We find the transformational leadership of the moon character can improve employee performance. Because the leaders always emit the moonlight form of new enthusiasm, harmonization, comfort, and coolness, the employee engagement behaviour becomes high. It has been rooted among employees that work orientation is noble. Involvement will be meaningful if there is an intelligent proactive role by the employee and the employee's performance becomes quality.